Durability Performance of Concrete Incorporating Two Diverse Aggregates Acquired From Şanlıurfa Quarries - Danışman, Emre; Ghatte, Hamid Farrokh (Bursa Teknik Üniversitesi, 2025)
In recent decades, Türkiye has dramatically increased the use of concrete as a main construction material and has become the leader among European concrete-producing countries. Therefore, the preparation of proper material for concrete is one of the great changes in terms of using sustainable components in concrete. Türkiye has considerable aggregate resources owing to its extensive mountains, which sets a foundation for investigating the aggregates. The granulometry of rock samples is one of the main sources of the aggregates. By employing the experimental methodology, the current study examines and compares the physical, mechanical and chemical properties of aggregates and the granulometry of rock samples from Seferoğlu quarry and Yetimoğlu quarry in Şanlıurfa province. For this purpose, physical properties were determined by specific gravity, volumetric weight, organic matter determination, alkali-silica rectification, freeze-thaw resistance, Los Angeles abrasion, high-temperature experiment, capillary water permeability, ultrasonic velocity measurement and pressure test. Calculating the concrete mix according to the ASTM standard prepared cubic concrete compressive strength of 15x15x15 cm. The results of compressive strength of 7 and 28 days of concrete were obtained. The results revealed that the aggregates demonstrated better physical and mechanical properties concerning the depletion of natural aggregates.
Keywords: Construction Materials; Yapı Malzemeleri